How is the Acceptance of the E-Laman Hati as an Animal Health Reporting Application in Bandung? - Yuriaan, Billy; Yasirandi, Rahmat; Suwastika, Novian Anggis (My University, 2024)
E-Laman Hati, an animal health reporting system implemented in the city of Bandung, serves as a vital platform for the systematic collection, analysis, and dissemination of information related to the health status of animals. This paper presents a usability assessment of the E-Laman Hati application, focusing on enhancing user services and ease of interaction. The System Usability Scale (SUS) is used as a key metric to evaluate the application's ease of use. The study employs Cronbach's Alpha values to gauge internal consistency, revealing strong reliability across all ten assessment items (Q1 to Q10), with calculated values ranging from 0.688 to 0.718 (greater than 0.6). Additionally, the validity product moment test demonstrates robust and consistent relationships between variables, affirming the reliability of the test in assessing intended constructs. The correlation coefficients (r-count) for questions Q1 to Q10 ranged from 0.396 to 0.648, surpassing the critical threshold of 0.202. The results of the SUS evaluation indicate an impressive average score of 94.548, positioning the application within the "Grade A"category of SUS grading guidelines. This rating reflects an exceptionally high level of usability, meeting, and exceeding user expectations. The success of the summarization approach in meeting user requirements is further affirmed by the positive evaluation derived from the SUS Score. Overall, E-Laman Hati emerges as a highly effective and user-friendly tool for animal health reporting in the urban context of Bandung.
Keywords: Bandung City; Point of Sales; System Usability Scale (SUS)